Manajemen Pendidikan Pada Masa Rasulullah Sampai Khulafau Rasyidin Dan Aplikasinya Di Era Millenial: Manajemen Pendidikan Pada Masa Rasulullah Sampai Khulafau Rasyidin Dan Aplikasinya Di Era Millenial - Suheri; Zaenuri; Adindan, Wiwik; Mahbub Ali, Amum; Anshori, Irfan (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2024)
Educational management that is currently developing contains many crucial problems so that a reflection of ideal educational management is needed. This research aims to find out and understand how education was managed during the time of the Prophet to the Rasyidin Khulafau; and its application in the current era. The method used in this research is a qualitative method. This type of research is descriptive qualitative. Data collection techniques were obtained through interviews and documentation analysis which was not measured by numbers. This research was carried out over a period of 6 months; starting from January 2024 to June 2024. The subjects of this research include students, lecturers and religious figures. Data analysis techniques use the Miles & Huberman model; includes data reduction, data presentation and drawing conclusions. The data validity technique used in this research is the triangulation technique.  The results of this research are that someone who is in charge of education must have the characteristics of analyzing, planning, problem solving, predicting.  Apart from that, you must also have good management characteristics, measurable targets, optimal processes and appropriate targets. The managerial reflection of the Prophet's time has been continued into the current millennial era; such as only a leader must have a good personality, understand the concept of Islamic education management, understand management strategies, have long-term Islamic education planning, have a strong determination in managing human resources, have the attitude of an educational organizer, have the qualities of a leader and education supervisor.